2005
DOI: 10.1021/ja0559395
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Point between Dialkoxy Disulfides (ROSSOR) and Thionosulfites ((RO)2SS):  Prediction, Synthesis, and Structure

Abstract: Isomeric preference between cyclic dialkoxy disulfides and thionosulfites is governed by the ring size of the heterocycle. Rings smaller than seven atoms prefer the thionosulfite connectivity, whereas larger rings or acyclic analogues favor the unbranched dialkoxy disulfide structure. Density functional calculations were employed to predict the crossover point at which both constitutional isomers are of comparable stability. Follow-up synthesis provides the previously unknown eight-membered ring dialkoxy disul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
(115 reference statements)
0
16
0
Order By: Relevance
“…126 Detailed study of this reaction has shown that dialkoxy disulfide 184 in all cases is the major product; however, upon the introduction of triethylamine into the reaction mixture, other cyclic products Ð seven-membered thiosulfite 186 and 16-membered dimer 187 Ð can also form (Scheme 94).…”
Section: Scheme 93mentioning
confidence: 99%
“…126 Detailed study of this reaction has shown that dialkoxy disulfide 184 in all cases is the major product; however, upon the introduction of triethylamine into the reaction mixture, other cyclic products Ð seven-membered thiosulfite 186 and 16-membered dimer 187 Ð can also form (Scheme 94).…”
Section: Scheme 93mentioning
confidence: 99%
“…(D) Reaction of a diol with S 2 Cl 2 resulted in the first example of a stable and fully characterized cyclic dialkoxy disulfide under mild conditions. 11 (E) S 2 Cl 2 was reacted with 1,7-s-hydrindacenedione dioximes leading to the first example of bis [1,2,3]dithiazolo-s-indacene. 12 In this example, S 2 Cl 2 has also been found as a chlorinating agent.…”
Section: Preparationmentioning
confidence: 99%
“…2a ). Dialkoxydisulfide 28 , 29 and diaminodisulfide 30 32 have been investigated as sulfur transfer reagents since 1970s. However, unsymmetrical polysulfidation with disulfanyl motif has never been achieved owing to the sharp contradiction raised by sequential and selective cleavage of dual S-O(N) bonds.…”
Section: Introductionmentioning
confidence: 99%